Renoprotective effect of stevia residue extract on adenine-induced chronic kidney disease in mice. (September 2020) - Mehmood, Arshad; Zhao, Liang; Ishaq, Muhammad; Zad, Oumeddour Dounya; Zhao, Lei; Wang, Chengtao; Usman, Muhammmad; Lian, Yunhe; Xu, Meili
Graphical abstract: Highlights: STRE markedly improve oxidative, inflammatory related biomarkers and renal structure. STRE attenuated renal fibrosis in adenine-induced CKD mice. STRE modulate gut microbiota composition at some extent in adenine induced CKD mice. Abstract: The present study was performed to explore the renoprotective potential of a stevia residue extract (STRE) on a mouse model of adenine-induced chronic kidney disease (CKD). The mice were divided into five groups (n = 10): control, model, Po, STRE-1, and STRE-2. Adenine (0.20% in the normal diet for 3 weeks) was used to induce CKD. Allopurinol and STRE markedly restored the balance of functional, oxidative, and inflammatory biomarkers and improved the renal histopathology and ultrastructure compared to the Mod group. Moreover, STRE also attenuated the renal fibrosis by suppressing the TGF-β1/Smad and Wnt/β-catenin signalling pathways and improved the gut microbiota composition. The results of present study confirmed that STRE has a potential to attenuate renal injury caused by adenine and may be used to develop of nutraceutical products, warranting further studies to elucidate beneficial effects of STRE.